Metode Topsis Dalam Sistem Pendukung Keputusan Pemilihan Siswa Berprestasi - Sikumbang, Erma Delima; Muhammad, Indra Maulana (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Decision making in an educational institution is very important. The principal should take a decision based on calculations and long-term thinking so that decisions determining student achievement to be taken are not mistakes. Still some problems in determining student achievement, in determining student and student who achievement still intuitive, there is no optimal utilization in processing student value by using method TOPSIS, which maan can make easier for teacher to determine student academic achievement Precisely and rapidly, where the topsis method is the best alternative that has the shortest distance from the ideal ideal solution and furthest from the ideal negative solution. From the test results with alternative topsis 66 method with 3 criteria that is normative value, adaptive value, and productive value. Of the 66 alternatives.